Extracorporeal Therapies in Children with Acute Liver Failure: A Single-Center Experience - Gün, Emrah; Durak, Ayşen; Botan, Edin; Şimşek Pervane, Selen; Gurbanov, Anar; Balaban, Burak; Kahveci, Fevzi; Özen, Hasan; Uçmak, Hacer; Aycan, Fulden; et al. (Turkish Journal of Gastroenterology, 2022)
Background: The aim of this study is to determine the indication, timing, and administration of extracorporeal therapies such as total plasma exchange and continuous renal replacement therapy in children with acute liver failure or acute-on-chronic liver failure. Methods: This study is conducted as a retrospective, single-center study. Between January 2016 and December 2021, pediatric acute liver failure or acute-on-chronic liver failure patients for whom total plasma exchange and/or continuous renal replacement therapy was performed were included in this study. Results: Thirty-four children with acute liver failure or acute-on-chronic liver failure were included during the study period. The children comprised 14 (41.1%) males, and the median age of the patients was 54 months (5-21). Twenty-four patients (70.6%) had pediatric acute liver failure, and 10 patients (29.4%) had acute-on-chronic liver failure. Patients’ median model for end-stage liver disease and pediatric end-stage liver disease scores were 24.7/23.5, respectively. Total plasma exchange therapy was performed on all patients whereas continuous renal replacement therapy was performed on 13 patients (38.2%). The median duration of continuous renal replacement therapy was 2.5 days (2-24). The median number of the total plasma exchange sessions was 3 (1-20). The median length of stay in pediatric intensive care unit was 4.5 (2-74) days. Eleven (32.5%) patients had 1 or more improvements in hepatic encephalopathy scores after extracorporeal therapy. Eleven (32.5%) patients died. There was a significant difference between the survivors and non-survivors with respect to levels of albumin, ammonia, pediatric risk of mortality scores, and pre-hepatic encephalopathy scores. Liver transplantation was performed in 4 of 24 pediatric acute liver failure patients, and all of them survived. Conclusion: Total plasma exchange and continuous renal replacement therapy are life-saving, and both methods may reduce morbidity and mortality, also bridging to liver transplantation. Cite this article as: Gün E, Durak A, Botan E, et al. Extracorporeal therapies in children with acute liver failure: A single-center experience. Turk J Gastroenterol. 2023; 34(1): 73-79.